Early evidence of delayed oligodendrocyte maturation in the mouse model of mucolipidosis type IV - Molly Mepyans; Livia Andrzejczuk; Jahree Sosa; Sierra Smith; Shawn Herron; Samantha DeRosa; Susan A. Slaugenhaupt; Albert Misko; Yulia Grishchuk; Kirill Kiselyov (The Company of Biologists, 2020)
Mucolipidosis type IV (MLIV) is a lysosomal disease caused by mutations in the MCOLN1 gene that encodes the endolysosomal transient receptor potential channel mucolipin-1, or TRPML1. MLIV results in developmental delay, motor and cognitive impairments, and vision loss. Brain abnormalities include thinning and malformation of the corpus callosum, white-matter abnormalities, accumulation of undegraded intracellular 'storage' material and cerebellar atrophy in older patients. Identification of the early events in the MLIV course is key to understanding the disease and deploying therapies. The Mcoln1−/− mouse model reproduces all major aspects of the human disease. We have previously reported hypomyelination in the MLIV mouse brain. Here, we investigated the onset of hypomyelination and compared oligodendrocyte maturation between the cortex/forebrain and cerebellum. We found significant delays in expression of mature oligodendrocyte markers Mag, Mbp and Mobp in the Mcoln1−/− cortex, manifesting as early as 10 days after birth and persisting later in life. Such delays were less pronounced in the cerebellum. Despite our previous finding of diminished accumulation of the ferritin-bound iron in the Mcoln1−/− brain, we report no significant changes in expression of the cytosolic iron reporters, suggesting that iron-handling deficits in MLIV occur in the lysosomes and do not involve broad iron deficiency. These data demonstrate very early deficits of oligodendrocyte maturation and critical regional differences in myelination between the forebrain and cerebellum in the mouse model of MLIV. Furthermore, they establish quantitative readouts of the MLIV impact on early brain development, useful to gauge efficacy in pre-clinical trials.